2019
DOI: 10.1007/s40265-019-01071-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineering for Success: Approaches to Improve Chimeric Antigen Receptor T Cell Therapy for Solid Tumors

Abstract: While impressive clinical responses have been observed using chimeric antigen receptor (CAR) T cells targeting CD19+ hematologic malignancies, limited clinical benefit has been observed using CAR T cells for a variety of solid tumors. Results of clinical studies have highlighted several obstacles which CAR T cells face in the context of solid tumors, including insufficient homing to tumor sites, lack of expansion and persistence, encountering a highly immunosuppressive tumor microenvironment, and heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 153 publications
(136 reference statements)
0
20
0
Order By: Relevance
“…We observed that the NFATsyn promoter provides a combination of high induction and low-baseline expression levels. However, most CAR T cell-targeted antigens expressed on solid tumors are not exclusively expressed on tumors, but are also present in normal tissues, which might result in unwanted "on target/off tumor" toxicities [10]. Thus, low-baseline expression without CAR signaling is clearly of benefit in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the NFATsyn promoter provides a combination of high induction and low-baseline expression levels. However, most CAR T cell-targeted antigens expressed on solid tumors are not exclusively expressed on tumors, but are also present in normal tissues, which might result in unwanted "on target/off tumor" toxicities [10]. Thus, low-baseline expression without CAR signaling is clearly of benefit in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…However, further improvements using CAR T cells are needed to address solid tumors. Heterogeneous antigen expression, insufficient tissue homing, and limited persistence of CAR T cells at the tumor site, as well as the immunosuppressive tumor microenvironment (TME), are major barriers that need to be overcome in the context of solid tumors [9][10][11][12]. Systemic application of interleukins, for example, interleukin (IL)12, provided some anti-tumor activity, as demonstrated by tumor regression and prolonged survival in murine studies [13,14], but was also linked with severe systemic toxicities [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Current-generation CARs comprise an antibody single-chain variable fragment domain for tumor antigen binding; a spacer or hinge domain for length and flexibility; a TMD controlling membrane integration and potentially self-association; and intracellular costimulation and activation domains that provide signals for proliferation, survival and activation of T cell effector functions. Efforts to imbue CARs with optimal signaling properties have probed all of these domains in one way or another (Alabanza et al, 2017;Balakrishnan et al, 2019;James, 2018;Liu et al, 2015;Mata and Gottschalk, 2019;Rafiq et al, 2020) . The TMDs, however, have received little attention in systematic studies of CAR design.…”
Section: Introductionmentioning
confidence: 99%
“…The real question is how the CD19 CAR T cell therapy can be improved to retain the high clinical response rates while limiting both short-and long-term adverse events [9]. Therefore, it is best to consider the adverse events associated with the preparative chemotherapy regimen separately from the CD19 CAR T cell adverse events.…”
mentioning
confidence: 99%
“…Such strategies, if proven to not reduce the efficacy of the CD19 CAR T cells, would reduce any long-term non-B cell cytopenias, potential for secondary bone marrow-related malignancies, and the overall cost of the CD19 CAR T therapy. However, most investigators in the field have focused on strategies to improve the safety of the CD19 CAR T cells themselves [8,9]. There is clear evidence that the choice of CAR construct costimulatory cassette impacts the persistence and function of CAR T cells [10][11][12].…”
mentioning
confidence: 99%